Spatial Patterns of Deltaic Deposition/Erosion Revealed by Streaklines Extracted From Remotely‐Sensed Suspended Sediment Concentration. Issue 11 (31st May 2022) - Salter, Gerard; Passalacqua, Paola; Wright, Kyle; Feil, Sarah; Jensen, Daniel; Simard, Marc; Lamb, Michael P.
Abstract: Deltas are vulnerable landscapes, making it crucial to understand their spatial patterns of deposition/erosion. Here, we used patterns in suspended sediment concentration (SSC) measured by a NASA airborne spectrometer, AVIRIS‐NG, to infer deposition/erosion within Wax Lake Delta, Louisiana. Conceptually, change in SSC within a fluid parcel traveling downstream reflects settling and/or entrainment from the bed. We found that remotely‐sensed SSC displays curvilinear features, which we interpret as streaklines. We developed a semi‐automated technique for extracting streaklines using a cost function based on SSC and its geometric curvature. We measured SSC change along streaklines, which when combined with flow velocities obtained from a hydrodynamic model, allowed us to infer instantaneous deposition/erosion rates. These rates are realistic in magnitude and record coherent spatial patterns across the delta. Our novel method provides a promising avenue for relating spatial patterns of land change to flow conditions over wide areas in vulnerable deltas. Plain Language Summary: River deltas are naturally low‐lying, making them vulnerable to flooding due to sea‐level rise. Predicting which regions of a river delta will be most vulnerable in the future requires understanding of how their elevation will change due to deposition and erosion of sediment. Deposition and erosion are difficult to measure, and depend on factors such as sediment supply and flow conditions. Here, we developed a technique to use suspended sediment concentration measured from airborne imagery to infer deposition/erosion. We find coherent spatial patterns, which we relate to flow conditions and sediment supply. Our novel method provides a promising avenue for relating spatial patterns of land change to flow conditions over wide areas in vulnerable river deltas. Future airborne and satellite‐based measurements will provide new opportunities to apply these methods to other river deltas globally. Key Points: We used change in concentration along streaklines extracted from remote‐sensed imagery to infer instantaneous rates of deposition/erosion Our method accurately inverts for deposition rates when applied to synthetic data from a 2D advection‐settling model We obtained coherent patterns of deposition and erosion based on remote‐sensed imagery of Wax Lake Delta, Louisiana